PTU-086 Outcomes of all surgery for ulcerative colitis over a 12-month period at a tertiary referral ibd unit. (22nd June 2015) - Smart, C; Manship, TA; Warren, L; Scott, N; Botterill, I; Saunders, R; Sagar, P; Ford, A; O'Connor, A; Hamlin, J
Abstract : Introduction: 1/4 of patients with ulcerative colitis (UC) will require surgery. We describe an audit of indications and outcomes of UC surgery at LTHT a tertiary referral centre for pouch surgery. Method: Patients undergoing surgery for UC in 2013 were identified from surgical lists, IBD nurse post-op review and from histopathology database. Data were extracted from electronic records and case notes. Results: 42 cases, 38 with complete dataset, 25 (59.5%) males. Mean age 42 (range 18–91), mean age at diagnosis 33 (7–68). 21 (55%) had failed >3 therapies and 15 (39%) taking oral steroids at time of surgery. 0 E1 disease, 15 (39.5%) E2, 15 (39.5%) extensive colitis (E3), 8 (21%) extent unclear. 48 procedures on 38 patients within the 12 months, 32 (67%) were elective, 16 (33%) emergency. Of 16 emergencies 11 were sub-total colectomies for acute severe disease (5 open, 6 laparoscopic), 3 EUAs, 1 rectal stump dehiscence and 1 obstructing tumour. At 12 months 23 (61%) completed pouch surgery. Of 40 colectomies 27 (67.5%) were laparoscopic. Indications: failed medical therapy 78.9% (n = 30, one low grade dysplasia), cancer 7.9% (n = 3, 1 = panproctocolectomy transverse colon carcinoma, 1 = pouch with adenocarcinoma cuff, 1 = sub-total colectomy with tumour in rectal remnant), patient choice 5.3% (n = 2), perforation 2.6% (n = 1), other 5.3% (n = 2) One death from pneumonia following emergency procedure. 11 short-term complications in 7 patients having 2-stage pouch surgery (5 wound infections, 2 anastomotic leaks, 1 ileus, 1 chest infection, 1 failure to restore continuity, 1 ureteric damage). 5 had longer-term complications (1 each for pouch dysfunction, high output stoma, strictured anastomosis, pouchitis, peri-anal pain). 7/16 having 3-stage pouch suffered one or more short-term complications (5 wound infection/dehiscence, 5 intra-abdominal complication (collection/sepsis/bleed), 2 ileus and one each of anastomotic leak, chest sepsis, VTE, rectal stump complication, AKI, confusion, pneumaturia, anterior spinal artery infarct). 7/16 patients suffered one or more longer-term complication (3 high output stoma before reversal ileostomy, anaemia n = 2 and and 1 of rectal discharge, SBO, adrenal insufficiency and retrograde ejaculation) Conclusion: Leeds is a high volume surgical unit performing 23 pouch operations in 12 months compared with the median number of 4 (national IBD audit). Most were laparoscopic as recommended by the IBD service standards. Pouch surgery carries significant short and long term risks and these should be addressed carefully. We recommend that all elective UC surgical patients are discussed at the IBD MDT and ideally reviewed in the combined clinic. Disclosure of interest: None Declared.